Optimizing the empowerment of rural agricultural communities in creating healthy agricultural villages based on agronursing - Rismawan Adi Yunanto; Aura Najwa Salsabila; Salma Maysaroh; Arya Adib Toni; Ninna Rohmawati; Candra Bumi (University of Merdeka Malang, 2024)
Heart disease is a leading cause of death globally, including in Indonesia, with an increasing prevalence in rural farming communities. Risk factors such as pesticide use, unhealthy diets, and poor lifestyles contribute to the high incidence of this disease. Communities in Bondowoso, East Java, especially farmers, need educational and training interventions to improve their knowledge and skills in preventing and treating heart disease. This program aims to improve the knowledge and skills of rural farming communities in the prevention, treatment, and early management of heart disease, including Cardiopulmonary Resuscitation (CPR) skills. The program is carried out through education on hypertension, heart disease, and heart diet, followed by practical training on CPR using audiovisual media and live demonstrations. The evaluation was carried out with a pretest and posttest to measure the increase in knowledge, as well as an assessment of practical skills. The results obtained were a significant increase in community knowledge measured from the results of the pretest and posttest, indicating the effectiveness of the education method. Community CPR skills also increased significantly after training and practical assessment. This program has succeeded in improving the knowledge and skills of rural farming communities in the prevention and treatment of heart disease, as well as CPR skills, which contribute to the long-term health of the community.